Evolution of the Maine Lobster Co-management Law - Acheson, James; Stockwell, Terry; Wilson, James (Maine Policy Review, 2000)
In fisheries management circles, there is growing realization that traditional ways of managing marine resources are not working and that new approaches to management need to be tried. One of the most promising of these new approaches is co-management, where authority for managing fish stocks is shared between the industry and government agencies. This paper discusses the implementation of the new co-management system, which was initiated in the Maine lobster industry in 1995. The law has clearly been successful; it has been framed in a way to allow lobster fishermen to be able to generate rules to constrain their own exploitative effort. At the same time, a number of problems have come to the fore, not least of which was the fact that passage of one regulatory measure caused problems for certain groups of fishermen who demanded remedial legislation. Thus, the co-management effort in Maine has moved ahead by solving a sequence of problems. But the fact that these problems are being solved places Maine in the forefront of jurisdictions experimenting with new ways to manage fisheries.
Keywords: Maine; lobster industry; fisheries management; co-management